Thickness of immediate dentin sealing materials and its effect on the fracture load of a reinforced all-ceramic crown - Ana Maria Spohr (2022)
Submitted by Biblioteca Suporte PUCRS (biblioteca.suporte@pucrs.br) on 2022-05-25T14:36:45Z No. of bitstreams: 2 Thickness_of_immediate_dentin_sealing_materials_and_its_effect_on_the_fracture_load_of_a_reinforced_allceramic_crown.pdf: 1035370 bytes, checksum: 4bfc315c5940101c05984dadda4245a1 (MD5) Thickness_of_immediate_dentin_sealing_materials_and_its_effect_on_the_fracture_load_of_a_reinforced_allceramic_crown.pdf: 1035370 bytes, checksum: 4bfc315c5940101c05984dadda4245a1 (MD5)